2014
DOI: 10.5812/jjm.9912
|View full text |Cite
|
Sign up to set email alerts
|

The Rise of Staphylococcal Super Antigens in Psoriatic Patients, a Case-Control Study

Abstract: Background:Staphylococcus aureus, the major virulence factor of hospital and community acquired infections, secretes numerous exotoxins (super antigens), which may affect immunological and inflammatory status in psoriatic skin lesion.Objectives:This study is designed to compare the S. aureus super antigens level in sera of psoriatic patients with normal cases (nevus).Patients and Methods:A case control study was performed in dermatology ward of Rasoul Hospital in Tehran, IR Iran (2008 - 2010). Staphylococcal s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 12 publications
(12 reference statements)
0
4
0
Order By: Relevance
“…Indeed, whereas SP had no effect on the release of exoproteins by S. epidermidis , SP stimulated the production of the Staphylococcal enterotoxin C2 by S. aureus MFP03. It is particularly interesting to note that Staphylococcal enterotoxins are members of a family of bacterial toxins that are increased in S. aureus strains associated with atopic dermatitis (Nada et al, 2012 ), psoriasis (Atefi et al, 2014 ), and even diabetic foot ulcers (Vu et al, 2014 ). In parallel, in S. aureus SP induced a decrease in the production of a lipase, whereas the lipase precursor accumulated suggesting that under the influence of SP, the precursor was not processed.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, whereas SP had no effect on the release of exoproteins by S. epidermidis , SP stimulated the production of the Staphylococcal enterotoxin C2 by S. aureus MFP03. It is particularly interesting to note that Staphylococcal enterotoxins are members of a family of bacterial toxins that are increased in S. aureus strains associated with atopic dermatitis (Nada et al, 2012 ), psoriasis (Atefi et al, 2014 ), and even diabetic foot ulcers (Vu et al, 2014 ). In parallel, in S. aureus SP induced a decrease in the production of a lipase, whereas the lipase precursor accumulated suggesting that under the influence of SP, the precursor was not processed.…”
Section: Discussionmentioning
confidence: 99%
“…They detected toxins in 96.8% of S. aureus isolates in lesional skin and 42.3% of S. aureus isolates in nonlesional skin. Also, Atefi et al, 2014 29 measured S. aureus toxins in the sera of a group of psoriasis patients. TSST was detected in 47% (20/41) of cases, significantly higher than in controls 6% (1/28), (P<0.0001).…”
Section: Discussionmentioning
confidence: 99%
“…This hypothesis is supported in the study by Balci et al [ 18 ], showing that there is an increased prevalence of toxigenic strains in the skin lesions of psoriatic patients compared to healthy subjects. Atefi et al [ 30 ] also confirmed, in a case-control study, that psoriatic patients have a higher frequency of staphylococcal superantigens measured in serum. In particular, there was a statistically significant difference between psoriatic patients and controls, considering Toxic Shock Syndrome Toxin (TSST), 47% vs. 6%, respectively, and Enterotoxins (A, B, D), 48.8% vs. 6%, respectively.…”
Section: Introductionmentioning
confidence: 88%